2019
DOI: 10.1159/000497617
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccine: Updates and Highlights

Abstract: HPV is the most common sexually transmitted biological agent and is the cause of many conditions in men and women, including precancer lesions and cancer. Three prophylactic HPV vaccines targeting high-risk HPV types are available in many countries worldwide: 2-, 4- and 9-valent vaccines. All the 3 vaccines use recombinant DNA technology and are prepared from the purified L1 protein that self-assembles to form HPV type-specific empty shells. This non-systematic review aims to summarize the HPV epidemiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 72 publications
0
47
0
1
Order By: Relevance
“…The efficacy of the HPV vaccination program is based mainly on the coverage of vaccination and the prevalence of HPV species in the population. We have shown that the HPV prevalence is different in the most populated (Table 2) [2,[4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The efficacy of the HPV vaccination program is based mainly on the coverage of vaccination and the prevalence of HPV species in the population. We have shown that the HPV prevalence is different in the most populated (Table 2) [2,[4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 85%
“…HPV is a circular double-stranded DNA virus that belongs to the Papillomaviridae family with more than 200 types, classified into 5 genera: α, β, γ, μ, and ν. Thirteen Acta Cytologica 2020;64:420-424 DOI: 10.1159/000506725 members of the α genus are classified as oncogenic or high-risk (HR)-HPV by the International Agency for Research on Cancer. HPV-16 is the most frequent oncogenic HPV type (3.2%), followed by HPV-18 (1.4%), HPV-52 (0.9%), HPV-31 (0.8%), and HPV-58 (0.7%) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-risk genotypes 6 and 11 mainly cause cervical, vulvar and vaginal low-grade lesions, and are responsible for 90% of the anogenital warts or condyloma acuminatum. [1][2][3] Vaccination represents one of the most cost-effective public health measures. The development of the prophylactic vaccine against HPV, with the aim of preventing the initial infection and subsequent neoplastic transformation, has generated some controversy.…”
Section: Introductionmentioning
confidence: 99%
“…The nonavalent vaccine in the two-dose scheme replaced the quadrivalent vaccine in January 2017, and has been covering girls aged 10 years. [2][3][4][5][6] Vaccination in males is recommended by several national and international scientific societies, and its introduction into the immunisation schedule is currently being discussed in Portugal.…”
Section: Introductionmentioning
confidence: 99%